2005
DOI: 10.3349/ymj.2005.46.1.181
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis of Transitional Cell Carcinoma to the Lower Abdominal Wall 20 Years after Cystectomy

Abstract: Iatrogenic implantation has been the main cause in the majority of cases of transitional call carcinoma (TCC) with metastasis to the abdominal wall. A 66-year-old woman had undergone radical cystectomy 20 years prior to presenting. Radiological investigations revealed one mass in the left lower abdominal wall and one mass in the right inguinal area. She underwent wide excision of the lesions that revealed metastasis of TCC. This report describes this case of a woman with bladder carcinoma who developed a metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…There are four mechanisms of metastatic dissemination by which the skin may be involved: 1) direct invasion from an underlying neoplasm, 2) iatrogenic implantation from an operation, 3) lymphatic spread, or 4) hematogenous spread [2,9]. In this case, similar to a patient reported by Ku et al [8], skin metastasis was likely by hematogenous spread rather than other mechanisms. However, brain and skin metastasis is regarded as a late manifestation of systemic spread.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…There are four mechanisms of metastatic dissemination by which the skin may be involved: 1) direct invasion from an underlying neoplasm, 2) iatrogenic implantation from an operation, 3) lymphatic spread, or 4) hematogenous spread [2,9]. In this case, similar to a patient reported by Ku et al [8], skin metastasis was likely by hematogenous spread rather than other mechanisms. However, brain and skin metastasis is regarded as a late manifestation of systemic spread.…”
Section: Discussionsupporting
confidence: 63%
“…According to the Brain Tumor Registry of Japan, only 0.6% of metastatic brain tumors were from bladder cancers [8]. In another study, central nervous system metastases were found in fewer than 1% of cases [1].…”
Section: Discussionmentioning
confidence: 99%
“…After resection of a high-grade bladder tumor, the most common cause of involvement of abdominal wall is iatrogenic implantation. [ 3 ] Such involvement may occur even without visible contamination of the surgical site or perivesical spread, likely cause being microscopic seedings. Some reports mention port site metastasis after laparoscopic and robotic surgeries for TCC.…”
Section: Discussionmentioning
confidence: 99%
“…presented a case of a 66-year-old woman with metastasis of TCC to the lower abdominal wall 20 years after radical cystectomy. [ 3 ] Salemis et al . presented a case of cutaneous metastasis 17 months after cystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The histology from skin recurrence was consistent with well-differentiated TCC. Subsequently patient developed a pelvic recurrence in spite of chemotherapy [ 10 ]. In our experience too the patient failed to respond to the cisplatin based chemotherapy as reported in above mentioned study.…”
Section: Discussionmentioning
confidence: 99%